Using Galant Schemata as Evidence for Universal Darwinism. (1st June 2013) - Jan, Steven
Abstract : The degree to which orthodox Darwinism is operative in culture is explored in order to determine the extent to which we may regard memetic phenomena as parallel (and therefore hard-Darwinian), not just analogous (and therefore soft-evolutionary) to those in genetics. Connections are drawn between certain natural processes and those hypothesized to be their equivalents in culture, specifically musical culture. To narrow the vast range of human music to a manageable sample, the focus is on the 'galant schemata' of the eighteenth century — recurrent, stereotypical musical figures which formed the focus of the training of numerous musicians of the period. The evidence supports Dawkins' claim of the existence of a 'Universal Darwinism' linking replicators in a variety of substrates by virtue of their dependence upon a common 'evolutionary algorithm', and it therefore also supports the validity of a memetic view of music.